2019
DOI: 10.11591/ijece.v9i5.pp3720-3731
|View full text |Cite
|
Sign up to set email alerts
|

Computational Sinc-scheme for extracting analytical solution for the model Kuramoto-Sivashinsky equation

Abstract: The present article is designed to supply two different numerical<br />solutions for solving  Kuramoto-Sivashinsky equation. We have made<br />an attempt to develop a numerical solution via the use of<br />Sinc-Galerkin method for  Kuramoto-Sivashinsky equation, Sinc<br />approximations to both derivatives and indefinite integrals reduce<br />the solution to an explicit system of algebraic equations. The fixed<br />point theory is used to prove the convergence of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In this paper, we will study a system of FODE which is a valid model for studying the development and growth of HIV, as we begin to define fractional derivatives and fractional integration. [20,21]. Previous studies have shown that there are many definitions of fractional derivatives, and here only we mention the method that we will use which is Caputo's definition, which is suitable for solving differential equations with initial values.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we will study a system of FODE which is a valid model for studying the development and growth of HIV, as we begin to define fractional derivatives and fractional integration. [20,21]. Previous studies have shown that there are many definitions of fractional derivatives, and here only we mention the method that we will use which is Caputo's definition, which is suitable for solving differential equations with initial values.…”
Section: Introductionmentioning
confidence: 99%